2019
DOI: 10.3389/fnins.2019.01089
|View full text |Cite
|
Sign up to set email alerts
|

Carbamazepine Alleviates Retinal and Optic Nerve Neural Degeneration in Diabetic Mice via Nerve Growth Factor-Induced PI3K/Akt/mTOR Activation

Abstract: Aim: Diabetic retinopathy causes loss of vision in adults at working-age. Few therapeutic options are available for treatment of diabetic retinopathy. Carbamazepine (CARB), a widely used antiepileptic drug, was recently accounted for its neuroprotective effect. Nerve growth factor (NGF) activates various cascades among which, PI3K/Akt/mTOR pathway has a vital action in NGF-mediated neuronal differentiation and survival. This study evaluated the effect of CARB in the treatment of diabetic retina and unveiled so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 70 publications
(87 reference statements)
0
13
0
Order By: Relevance
“…Akt and mTOR are considered survival and cellular growth in response to lesions. NGF, via trkA, activates PI3K/Akt and ERK/MAPK signaling pathways and the downstream mTOR, and this pathway mediates several NGF effects, such as endothelial cell invasion and cord formation during development (Park et al 2007), angiogenesis in subchondral bone (Yu et al 2019), and neuroprotection (Elsherbiny et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Akt and mTOR are considered survival and cellular growth in response to lesions. NGF, via trkA, activates PI3K/Akt and ERK/MAPK signaling pathways and the downstream mTOR, and this pathway mediates several NGF effects, such as endothelial cell invasion and cord formation during development (Park et al 2007), angiogenesis in subchondral bone (Yu et al 2019), and neuroprotection (Elsherbiny et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been demonstrated that carbamazepine activates NGF/PI3K/Akt/mTOR signaling in mice models of diabetic retinopathy. 9 This effect was never tested in any model of epileptogenesis, but it may result in a positive modulation of residual activity of the TSC and GATOR1 complexes in tuberous sclerosis and GATORopathies, with subsequent benefits on seizure control.…”
Section: Discussionmentioning
confidence: 99%
“…In the sixth day after the injection of alloxan, the fasting blood glucose (FBG) was measured using a One Touch Ultra Mini glucometer (USA) by applying a droplet of blood taken from the tail veins. The mice that had an FBG level greater than 200 mg/dL were counted as diabetic [ 46 ].…”
Section: Methodsmentioning
confidence: 99%